Ages of Jurassic volcano-sedimentary strata in the Yanshan Fold-and-Thrust Belt and their implications for the coal-bearing strata of northern China. Issue 8 (24th May 2019) - Gao, Hai-Long; Zhao, Yue; Zhang, Shuan-Hong; Liu, Jian; Ye, Hao; Wang, Guo-Can; Liu, Jian-Min
ABSTRACT: Jurassic coal-bearing strata are widely distributed in the North China Craton (NCC) and other areas of northern China. These coal-bearing strata were previously considered to be Early–Middle Jurassic in age based on plant fossils, particularly the fossil assemblage of Coniopteris – Phoenicopsis . Since coal-bearing strata are interbedded with volcanic units in the basins of the Yanshan Fold-and-Thrust Belt (YFTB), northern NCC, isotopic dating of the volcanic units can therefore provide age constraints on the coal-bearing strata and the Coniopteris ‒ Phoenicopsis assemblage. In this paper, we performed a systematic geological survey and present the results of zircon U–Pb dating of the volcanic units and a pluton in typical basins of the YFTB. These data, combined with the results of previous studies, indicate that the ages of the Nandaling/Xinglonggou, Haifanggou, Jiulongshan, and Tiaojishan/Lanqi formations are 180–168, 169–161, 161–157, and 161–153 Ma, respectively. The ages of the interbedded coal-bearing Yaopo and Beipiao formations are constrained to be 169–161 and 177–169 Ma, respectively. Our results demonstrate that both the coal-bearing strata and the Coniopteris ‒ Phoenicopsis assemblage are Middle Jurassic in age, which is younger than that previously considered. This fossil assemblage plays a critical role in age constraints on the Jurassic coal-bearing strata. The refinement of its age permits a more precise dating of the coal-bearing strata, especially in northwestern China, where datable interbedded volcanic units are lacking. Stratigraphical framework for the Jurassic strata of Yanshan region is established. The fossil assemblage of Coniopteris ‒ Phoenicopsis occurred in Middle Jurassic. The Jurassic coal-bearing strata in northern China are mainly Middle Jurassic.